The simulation of intermolecular interactions of carboxylic and amine groups with calcium carbonate - Abu Zar, Che Azimi; Norhayati, Abdullah; Fatmawati, Adam; Zulkafli, Hassan; Sunarti, Abd Rahman; Mohd Zulhaizan, Mohd Noor (UTM Press, 2023)
Surface facilities including tubing and valves at the oilfield have been plagued by mineral scale deposits, which are constitute of calcium carbonate (CaCO3). Penta-potassium diethylenetriaminepentaacetic acid salt (DTPA-K5) has a higher affinity for the metal cations complexes during the chelation process. The eight complexing sites (five carboxylate and three amines) empower the metal ion interactions. This work investigated the molecular dynamics simulations between the DTPA-K5 with the calcium carbonate, CaCO3 scale. The interaction was performed through molecular dynamic (MD) simulation using condensed phase optimised molecular potentials for atomistic simulation studies (COMPASS) force field and the Ewald summation method in Material Studio. The simulation trajectory files examined the intermolecular interactions for radial distribution function (RDF). The simulation shows strong DTPA-K5 with calcium interactions, which revealed the metal ion complexes contributing to the chelation process through the reactive carboxylic and amine functional groups, which were O7 == Ca at radius, r, 2.25 Å with g(r) of 10.09 and N1 -- Ca at radius, r, 2.25 Å with g(r) 2.51.